Pengaruh Perencanaan Pajak dan Penghindaran Pajak terhadap Nilai Perusahaan dengan Tranparansi Sebegai Variabel Moderasi (Studi Kasus pada Perusahaan Sektor Kuangan yang Terdaftar di Bursa Efek Indonesia dengan Transparansi Informasi Sebagai Variabel Moderasi) - Julasy, Cici Sonia; Safrianti, Sintia; Waliamin, Janusi (Universitas Batanghari, 2024)
The study aims to empirically examine and prove how tax planning and tax avoidance affect firm value, with information transparency as a moderating variable. This research utilizes a quantitative approach applied through causal research methods. The sample was selected using purposive sampling technique, and data analysis was performed using Eviews 12 software. The sample consists of 48 data points from 16 financial sector companies listed on the Indonesia Stock Exchange for the period 2020-2022. The data analysis technique employs multiple regression analysis and moderated regression analysis (MRA). The results of this study indicate that tax planning has no effect on firm value. Tax avoidance does not impact the value of the company. Information transparency can strengthen the effect of tax planning on firm value, and information transparency can enhance the impact of tax avoidance on a company's value.